INTERNAL CONTROL IN REFOCUSING AND USE OF DANUREJO MERTOYUDAN MAGELANG VILLAGE FUNDS IN PANDEMIC COVID-19 OUTBREAK - Fuad Yanuar AR (Universitas Tidar, 2020)
This study aims to measure and understand the effectiveness of internal control in refocusing and using village funds in the Danurejo village during the covid 19 pandemic based on PP No.60 Year 2008. This study uses a qualitative descriptive approach by collecting data through online interviews because it follows the health protocol due covid global pandemic 19. This study illustrates the internal controls carried out and explains the lack of reliability of financial statements and efforts to streamline internal control over the use of village funds for handling the Covid 19 pandemic based on PP No. 60 of 2008.